Visual behavior and the quality of decisionmaking on volleyball - Henrique de Oliveira Castro; Gibson Moreira Praça; Gustavo De Conti Teixeira Costa; Gustavo Ferreira Pedrosa; Pablo Juan Greco (Universidade Federal de Santa Catarina, 2016)
This study aims to verify the visual behavior using the analysis of both quantity and duration of visual fixation and the quality of the DM in volleyball players and athletes from other sports in extreming attacking (EA), cental attack (CA), setting (SE) and blocking (BL) situations. The visual behavior was analyzed during the evaluation of volleyball scenes with an eye-tracking system. The first decision the volunteer voiced was determined as his solution for the scene presented and it was used for analyzing the DM quality. For the quantity of visual fixations, the independent t-test was used to compare groups in the following situtations, EA, SE and BL. For analyzing the quality of DM, the chi-square test of proportions was used. Moreover, for the analysis of the duration and number of visual fixations, the independent t test was addopet (or Mann-Whitney test when some of the assumptions were not met for parametric analysis). Significantly higher values were observed on duration of visual fixations in athletes from other sports comparing to volleyball players at CA (p = 0.042). The DM were significantly different in EA (p = 0.024) and CA (p = 0.001) between groups, showing higher frequency of correct answers for the volleyball players. We conclude that volleyball players perform faster fixations in situations of CA and take more correct decisions in attacking situation (EA and CA) compared to athletes from other sports.